Penyebab Warga Menempati Bangunan Permanen di Tanah Milik PT KAI: Studi di Nagari Muaro, Kecamatan Sijunjung - Ahmad Darisman (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2019)
People continue to occupy permanent buildings built on land owned by PT Kereta Api Indonesia(PT KAI) in Nagari Muaro, Sijunjung District, in the context that the buildings are threatened withdisplacement due to the railway revitalization project. The objectives of this research are to describe howpeople able to access buildings on land owned by PT KAI and to undertatand thge reaons why they keepoccuoaying the buldings. In order to achieve the research objectives, a qualitative study wasconducted andused the social action theory proposed by Max Weber. The study found that people get get access to theciulding based on permission from employees of PT KAI, from previous occupants, purchasing the buildings,renting not to PT KAI, but to prervious occiers. They were aware that the land belongs to PT KAI, somepeople say that the land belongs to PT Ombilin.